Position of Victims in Corruption Crime at the Medan Corruption Court - Wessy Trisna; Ridho Mubarak (International Journal Reglement & Society (IJRS), 2020)
A victim is someone individually or jointly suffering from loss, including physical or mental injury, emotional suffering, economic loss or damage to his basic rights, which is caused by the actions of other parties who violate criminal law in a country, whether intentionally or because of negligence. So far, in handling corruption cases, the perpetrators and the law have always been highlighted, while victims are rarely paid attention. Legal protection for victims in criminal acts of corruption needs to be considered because the rights of victims who have good intentions are still being harmed. So it is necessary to discuss the position of the victim in a corruption case and the rights and obligations of the victim in a corruption case at the Medan Corruption Court. Thus, although the position of the victim in a criminal act of corruption based on the criminal justice system is still very weak, the victim has the right to apply for restitution or compensation if their social and economic rights are harmed by the occurrence of a criminal act of corruption